Distance and the Multinational Wage Premium - Udo Kreickemeier (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Combining administrative data on German workers with commercial data on German producers, we find evidence that German subsidiaries of foreign multinationals, while paying a premium relative to other local producers, offer wages of similar size as German subsidiaries of German multinationals. Zooming in on foreign multinationals gives a more nuanced picture and reveals a so far unexplored distance effect that is prevalent in the data. Foreign multinationals pay lower wages than German multinationals if the ultimate owner is located in close proximity to Germany, whereas the opposite is true if the ultimate owner is located further away. To provide a rationale for this pattern, we develop a theoretical model that allows for firm-specific wages and emphasizes uncertainty about foreign wage payments as an important factor of the foreign investment decision. Due to this uncertainty, firms that have to pay high wages at home are more likely to seek investment abroad. High-wage firms are also more likely to actually produce abroad, once the foreign wage level has been revealed, explaining why multinationals pay higher wages than non-multinationals in the home and the host country of investment. In the model, the empirically observed distance effect on the multinational wage premium occurs since exporting as an alternative means of reaching foreign customers is less attractive for distant locations, and firms are therefore more willing to accept unfavorable (i.e. high wage) draws for foreign production in locations that are further away from their headquarters.
Keywords: F12; F14; F21; F23; 330; Multinational Wage Premium; Heterogeneous Firms; Distance Effects